1992
DOI: 10.1128/mcb.12.3.1021
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent regulation of a heterologous transcriptional activation domain fused to yeast heat shock transcription factor.

Abstract: The heat shock transcription factor (HSF) of the yeast Saccharomyces cerevisiae is posttranslationally modified. At low growth temperatures, it activates transcription of heat shock genes only poorly; after shift to high temperatures, it activates transcription readily. In an effort to elucidate the mechanism of this regulation, we constructed a series of HSF-VP16 fusions that join the HSF DNA-binding domain to the strong transcriptional activation domain from the VP16 gene of herpes simplex virus. Replacement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 38 publications
(51 reference statements)
1
63
0
1
Order By: Relevance
“…However, while the C-terminal AD from yeast Hsf is sufficient to strongly drive gene expression when fused to a heterologous DNA binding domain, this activator is repressed at low temperatures in the native context of Hsf in spite of constitutive DNA binding (Sorger, 1990). Further, even when the Hsf C-terminal AD is replaced with a heterologous AD, this Hsf∆C-AD fusion retains near wild type activity under basal and heat shock conditions, though intergenic mutants can bypass basal repression of this fusion (Bonner et al, 1992). These observations suggest that interdomain interactions restrain Hsf activity in the absence of stress.…”
Section: Chapter 1: Introduction To Proteostasis and The Conserved Hementioning
confidence: 70%
See 1 more Smart Citation
“…However, while the C-terminal AD from yeast Hsf is sufficient to strongly drive gene expression when fused to a heterologous DNA binding domain, this activator is repressed at low temperatures in the native context of Hsf in spite of constitutive DNA binding (Sorger, 1990). Further, even when the Hsf C-terminal AD is replaced with a heterologous AD, this Hsf∆C-AD fusion retains near wild type activity under basal and heat shock conditions, though intergenic mutants can bypass basal repression of this fusion (Bonner et al, 1992). These observations suggest that interdomain interactions restrain Hsf activity in the absence of stress.…”
Section: Chapter 1: Introduction To Proteostasis and The Conserved Hementioning
confidence: 70%
“…shown that expression of chimera containing the Hsf1 DNA binding domain fused to a viral transcriptional activator results in constitutive expression of Hsf1 targets (Bonner et al, 1992). Thus, we replaced the Gal4 DNA binding domain in our GEM construct with …”
Section: Unsurprisingly Cells Expressing Thismentioning
confidence: 99%
“…Several ''masking'' domains have been identified. These include an N-terminal repressor domain (Sorger 1990), a region that overlaps the DNA-binding and trimerization domains (NietoSotelo et al 1990;Bonner et al 1992;Chen and Parker 2002), and a heptapeptide sequence termed CE2 located adjacent to the C-terminal activation domain ( Jakobsen and Pelham 1991). While these have been traditionally thought to physically interact with one or both activation domains, the possibility of alternative or additional mechanisms of repression, including the recruitment of corepressors, has not been ruled out.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental rationale: The ability of yeast HSF to activate transcription in response to thermal stress, and the role of its activation and regulatory domains in this process, have been extensively investigated (e.g., NietoSotelo et al 1990;Sorger 1990;Bonner et al 1992;Bulman et al 2001;Chen and Parker 2002;Erkine and Gross 2003;Hashikawa and Sakurai 2004). However, a poorly understood function of HSF is its ability to stimulate basal transcription.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, a mutation in the DNA-binding domain causes constitutive activity, albeit in a fusion protein where the CTA had been exchanged with a heterologous activator (Bonner et al, 1992).…”
Section: Introductionmentioning
confidence: 99%